How do Entrepreneurial Human Resource Practices Determine Small Firmsâ Performance? - Sulaimiah, Sulaimiah; Sulhaini, Sulhaini (Universitas Prasetiya Mulya, 2016)
This study examines the effects of entrepreneurial human resource practices on market-oriented behaviour, relational capability, and business performance at small-sized firms. For the purpose of the study, a survey was carried out for two different product types, namely handi crafts and food/drink, and sample firms were purposively selected. Interestingly, the findings suggest that, though practices may not directly improve firmsâ performance, implementing practices characterised by entrepreneurial orientation is a start for high performance as market oriented behaviour and relational capability moderate the effects. The practices stimulate employeesâ mind-sets, shaping their behaviour and willingness to find new ways of doing business and satisfying external customers. The implication of the study was that such practices should be designed to improve small firmsâ market-oriented behaviour and relational capability for better business performance.Keywords:Â Entrepreneurial Human Resource Practices, Relational Capability, Market Orientation, Business PerformanceÂ Â https://doi.org/10.21632/irjbs.9.2.133-146Â